CONDITION AND DYNAMICS OF CEDAR FORESTS OF WESTERN SIBERIA (TOMSK REGION) - Myasnikov, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The first and only annotated index of the domestic literature on cedar for 1755–1957 «Cedar forests and integrated use» was compiled by well-known local historian M.F. Petrov and published in Sverdlovsk in 1961. The index includes 614 works combined into 7 sections: fruiting of cedar forests, pine nuts, resin tapping of cedar, physicochemical properties of cedar wood, natural regeneration and cedar cultures, insect pest and complex use of cedar forests. Interest in study and use of cedar forests increased sharply after the decree of the Council of Ministers of the RSFSR of October 26, 1957 «On measures to improve the use of cedar plantations, development of handicrafts and increase in harvesting of pine nuts, fur peltries, upland fowl and wild berries» and the All-Russian scientific and production conferences about cedar problems in September 1959 in Novosibirsk and in August 1969 in Tomsk. In the central and northern parts of the Tomsk region Siberian Cedar (Pinus sibirica Du Tour) forms large forests and is present in the plantations of all the main forest-forming species. In 1989, the cutting of cedar was prohibited and therefore, there was an increase in the area of forests of this species in the region, but a decrease in the area of cedar forests is due to forest fires, diseases and forest pests. In this paper the assessment of state and dynamics of Siberian Cedar in Tomsk region was made, that allows estimate economic and environmental importance of cedar forests in the region.